Experimentally testing asymptotically safe quantum gravity with photon-photon scattering - Eichhorn, Astrid (Arxiv, 2012)
Matter-quantum gravity interactions can be used for direct and also indirect experimental tests of quantum gravity. We focus on photon-photon scattering in asymptotically safe gravity as a direct test of the small-scale structure of spacetime, and discuss how near-future experiments can probe asymptotic safety in a setting with large extra dimensions.
Gesehen am 11.01.2018